Appropriateness of Language Used in Patient Educational Materials from 24 National Anesthesiology Associations. (December 2016) - Govender, Denira; Villafranca, Alexander; Hamlin, Colin; Hiebert, Brett; Parveen, Divya; Jacobsohn, Eric
Abstract : Background: Patient education materials produced by national anesthesiology associations could be used to facilitate patient informed consent and promote the discipline of anesthesiology. To achieve these goals, materials must use language that most adults can understand. Health organizations recommend that materials be written at the grade 8 level or less to ensure that they are understood by laypersons. The authors, therefore, investigated the language of educational materials produced by anesthesiology associations. Methods: Educational materials were downloaded from the Web sites of 24 national anesthesiology associations, as available. Materials were divided into eight topics, resulting in 112 separate passages. Linguistic measures were calculated using Coh-Metrix (version 3.0; Memphis, USA) linguistic software. The authors compared the measures to a grade 8 standard and examined the influence of both passage topic and country of origin using multivariate ANOVA. Results: The authors found that 67% of associations provided online educational materials. None of the passages had all linguistic measures at or below the grade 8 level. Linguistic measures were influenced by both passage topic ( F = 3.64; P < 0.0001) and country of origin ( F = 7.26; P < 0.0001). Contrast showed that passages describing the role of anesthesiologists in perioperative care used language that was especially inappropriate. Conclusions: Those associations that provided materials used words that were long and abstract. The language used was especially inappropriate for topics that are critical to facilitating patient informed consent and promoting the discipline of anesthesiology. Anesthesiology associations should simplify their materials and should consider screening their materials with linguistic software before making them public. Abstract : Twenty-four national anesthesia society Web sites were explored, and 67% provided online information. All material was above grade 8 level ( i.e., too complex for lay comprehension), especially text describing the anesthesiologist's role. Such materials should be simplified and validated.